Occupational Safety and Health Practices of Selected Private Higher Education Institutions in the Philippines - Estadilla, Lorraine (The Indonesian Institute of Science and Technology Research, 2025)
Higher education institutions (HEIs) are as important as other workplace settings. During the COVID-19 pandemic, the Commission on Higher Education (CHED) and the Department of Health (DOH) put a premium on the safety and health of all HEI stakeholders. This research determines the occupational safety and health (OSH) practices of HEIs in Region V to assess how far they have started and implemented health and safety measures for the well-being of all employees. A descriptive–evaluative method was utilized in conducting this study. Questionnaires and documentary analysis were used as data-gathering tools. The prevalence of OSH practices was high in the six HEIs selected in Region V. There was also a significant difference in the appraisals of stakeholders, even if they rated the indicators as highly practiced. The challenges cited were least experienced by the stakeholders, specifically, regulations to ban and control dangerous products, low public awareness of OSH, recurrent fluctuations in the amount of work, and conflicting work demands. There is a need to consult employees in policy formulation to increase participation. Having adequate facilities not only protects workers from hazards but also increases workers’ productivity. Safe and adequate facilities are needed to encourage employees to go to work because they need to know that they can still attend to their personal needs while at school. Staff require information and training to operate safely without putting their health at risk.